Analysis of Total Phenol from Sentul Fruit Extraction (Sandoricum koetjape Merr.) - Faizul Bayani (Universitas Pendidikan Mandalika, 2021)
Studies on Sentul fruit have identified the presence of phenolic compounds in the flesh and have not yet analyzed the total phenolic content. This encourages research to conduct further analysis of the total phenol of Sentul fruit, this is to optimize the value of its benefits, especially in the health sector so that its use can be increased as phytopharmacology drugs. Extensive laboratory studies were carried out with sample preparation and qualitative analysis of total phenol. Determination of the total phenol content contained in the sample extract was carried out based on the Folin-Ciocalteu method. In the end, in this study we can conclude that the total phenolic content of the crude extract of ripe Sentul fruit pulp showed positive results in various sample treatments. Further results are explained in this article.